The impact of diabetes mellitus on the osseointegration of absorbable screws: an animal experimental investigation - Wu, Zelin; Xiao, Lei; Hou, Huige; Li, Ling; Gao, Yanping; Guan, Jian; Chen, Jiwen; Zeng, Lingfeng; Chen, Zihang; Mok, Tsz-Ngai; Miao, Guiqiang; Zheng, Xiaofei; et al. (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aims to explore the correlation between alterations in blood glucose levels and the osseointegration as well as biomechanical properties of nHA/PLLA absorbable screws, and elucidate the impact of DM on bone metabolism surrounding nHA/PLLA absorbable screws. 75 rats were randomly assigned to either the Diabetes mellitus (DM) group and the control group. DM was induced in rats through intraperitoneal injection of 1% streptozotocin. A single nHA/PLLA absorbable screw was surgically implanted into the medial tibia of each rat in both groups. Rats were euthanized at 4 weeks, 8 weeks and 12 weeks post-implantation, and tissue specimens were subjected to histological, histomorphological, Micro-CT scan, biomechanical, microindentation mechanical testing of trabeculae bone, Raman spectroscopy, and Western blot analyses. Changes in bone mass, trabeculae structure, composition, mechanical properties, and expression of bone formation-related proteins around the absorbable screws were compared between the two groups at the microscopic, biomechanical, and molecular levels. The results show that DM disrupts the trabeculae structure surrounding absorbable screws, leading to alterations in trabeculae bone composition, diminished mechanical properties, and impaired bone metabolism. DM significantly compromises osseointegration at the absorbable screw-bone interface and diminishes bone quality in the vicinity of the absorbable screw.